(untitled) (Zoological Archives: An International Journal, 2022)
Herbivory in mammals has evolved through two primary digestive strategies – foregut fermentation, in which microbial breakdown of plant cell walls occurs in specialised pre-gastric chambers before enzymatic digestion, and hindgut fermentation, in which microbial fermentation follows enzymatic digestion in the caecum and proximal colon – each with distinct energetic efficiencies, dietary optima, and body size constraints that have shaped herbivore ecology and evolution across diverse mammalian lineages. Despite the centrality of digestive strategy to herbivore biology, the quantitative physiological differences between fermentation strategies and the ecological and phylogenetic determinants of strategy adoption remain incompletely characterised across a fully comparative mammalian dataset. This study presents the most comprehensive comparative analysis of herbivorous mammal digestive physiology yet conducted, measuring 14 digestive tract morphometric and functional parameters on 247 individuals from 84 species representing 18 families across foregut fermenters, hindgut fermenters, and non-specialised herbivores. Foregut fermenters showed significantly higher fibre digestibility (mean 68.4% vs. 47.4% neutral detergent fibre digestibility; p < 0.001) but lower passage rate (mean retention time 48.4 vs. 24.7 hours), confirming the efficiency-speed trade-off. Body mass was a significant negative predictor of the foregut advantage in fibre digestibility – above approximately 600 kg body mass, hindgut fermenters achieve comparable fibre digestibilities to foregut fermenters, explaining why large-bodied herbivores (horses, rhinos, elephants) are predominantly hindgut fermenters despite apparently lower efficiency. Phylogenetic signal in digestive strategy was moderate (Blomberg’s K = 0.64) – confirming that strategy adoption is substantially determined by ecology and body size rather than phylogenetic inertia alone.